Analysis of Prestressed Concrete Bridges Constructed by the Cantilever Method in Service Stage - الوادي محمد هاجم; ادلبي رأفت; حداد حسام (Latakia University Journal -Engineering Sciences Series, 2020)
The research presents a proposed algorithm for calculating time-dependent deformations in bridges constructed by cantilever method. In this algorithm, creep deformations are analyzed using "Age-Adjusted Effective Modulus" and Principle of Superposition, Also the forces resulting from these deformations are calculated. The proposed algorithm was used to create a computer program to calculate these deformations. This program was used to analyze the Kędzierzyn-Koźle bridge in Poland. The results showed the importance of the additional forces resulting from the time-dependent deformations and the need to take them into account in the design.